PsycEXTRA Dataset 2006
DOI: 10.1037/e650712007-001
|View full text |Cite
|
Sign up to set email alerts
|

Criminal Careers Up to Age 50 and Life Success Up to Age 48: New Findings from the Cambridge Study in Delinquent Development

Abstract: The Home Office Research Studies are reports on research undertaken by or on behalf of the Home Office. They cover the range of subjects for which the Home Secre t a ry has re s p o n s i b i l i t y. Other publications produced by the Research, Development and Statistics include Findings, Statistical Bulletins and Statistical Papers. RDS is part of the Home Office. RDS staff are embedded within delivery groups working closely with front-line staff. The HO Chief Scientific Advisor, who is also Director of RDS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
236
0
16

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 204 publications
(273 citation statements)
references
References 27 publications
13
236
0
16
Order By: Relevance
“…This view is supported by other studies showing that IPV perpetration is associated with other forms of criminality (e.g. Felson & Paré, 2005), youth violence (e.g., Herrenkohl et al, 2007), middle-school aggression (e.g., O'Donnell et al, 2006), general violence (e.g., Farrington et al, 2006), violent offending (e.g., Thornton, Graham-Kevan & Archer, 2010), and bullying (e.g., Corvo & DeLara, 2009). It is further supported by the longitudinal study of Moffitt et al (2001), who found that the strongest risk factor for IPV perpetration, for both sexes, was a record of violent delinquent behavior.…”
Section: Discussionsupporting
confidence: 65%
“…This view is supported by other studies showing that IPV perpetration is associated with other forms of criminality (e.g. Felson & Paré, 2005), youth violence (e.g., Herrenkohl et al, 2007), middle-school aggression (e.g., O'Donnell et al, 2006), general violence (e.g., Farrington et al, 2006), violent offending (e.g., Thornton, Graham-Kevan & Archer, 2010), and bullying (e.g., Corvo & DeLara, 2009). It is further supported by the longitudinal study of Moffitt et al (2001), who found that the strongest risk factor for IPV perpetration, for both sexes, was a record of violent delinquent behavior.…”
Section: Discussionsupporting
confidence: 65%
“…However, when analyzing life success among active offenders, the study shows that at age 32, only 42 % of all persistent offenders lived successful lives, compared to 90 % of those who were not convicted. At age 48, despite an overall increase in life success, the percentage of persisters living a successful life was still the lowest by far [17].…”
Section: Adult Outcomes Of Vulnerable Youthsmentioning
confidence: 99%
“…This is especially so for those with a more extensive criminal history (e.g. [17]). However, some important features of the currently available studies potentially limit the generalizability of these conclusions.…”
Section: Adult Outcomes Of Vulnerable Youthsmentioning
confidence: 99%
See 2 more Smart Citations